Kegiatan 10 Hari Ramadan Menghafal Al-Qur’an sebagai Program Unggulan pada Pondok Pesantren Ulul Albaab Jeneponto - Rosmita Rosmita; Nasaruddin Nasaruddin (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
One of the Islamic boarding schools located in Jeneponto Regency, South Sulawesi, is the Ulul Albaab Islamic Boarding School. Ulul Albaab Islamic Boarding School focuses on fostering memorization and teaching of the Koran. The purpose of the STIBA Makassar Community Service Study Program batch V is as a form of community service which is a pillar of the Tri Darma of Higher Education in Indonesia. The method of implementing community service at the Ulul Albaab Islamic Boarding School begins with mapping the problems and needs of the Islamic boarding school using an instrument that is made in a simple way, namely SOAR analysis. Class V STIBA Makassar KKN students who are placed in Jeneponto Regency have carried out several work programs to improve the quality of human resources, especially students at the Ulul Albaab Jeneponto Islamic Boarding School. Among the work programs are the 10 Days of Ramadan Memorizing the Koran, Teaching Arabic, and Spreading Masks. Activities 10 Days of Ramadan Memorization of the Koran is PP's flagship program. Ulul Albaab Jeneponto. The activity aims to increase and strengthen the memorization of the activity participants, as a means for participants to take advantage of the time in the month of Ramadan by memorizing the Koran. The results of the study were 2 students memorized 2 juz, 2 students memorized 1 juz, and some participants managed to memorize half a juz and the formation of 5 tahfiz groups, 5 Arabic language groups from among the students.